Invited Lecture 2: Endocrine disrupting chemicals in ocean ecosystem and human health risks - Atanu Sarkar (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch He is the author of 5 books and edited 7 books (chapters). He has published peer-reviewed articles in several reputed journals. He is serving as a Course Coordinator for Undergraduate (MD) teaching: Environmental health. There are 2 notified research grants in his credit: CIHR Project Grant (Spring 2019) and NSERC along with 3 ongoing projects. He was awarded Faculty of Medicine, Memorial University Outstanding Research Excellence Award (2015) and SSHRC Travel Grants Competition, Annual conference of International Society of Environmental Epidemiology, Basel, Switzerland (2013). His area of research interest is Environmental contamination and ecosystem health, Climate change and health, Indigenous health, Global Health and Social epidemiology. Endocrine disrupting chemicals (EDCs) are the exogenous substances that can cause adverse health effects through disruption to the body's endocrine systems. This can result in changes to circulating hormone concentrations, which act as signals to regulate growth, metabolism and reproduction. Hormones are maintained at very low concentrations in the bloodstream; therefore, even low levels of EDC exposure can have large consequences on endocrine homeostasis. The potential adverse health effects resulting from exposure to EDCs, including developmental abnormalities, abnormal hormonal profiles, disorders of the reproductive systems, increased incidence of cancer, and alterations to both the immune and nervous systems. There are numerous chemicals used in our day to day basis have endocrine disruption property, such as pesticides, flame retardants, and various other industrial chemicals. Humans are exposed to those chemicals from direct exposures while using them, and also from the diet. EDCs reach environment from deposition via industrial effluents or direct application and also through wastewater and landfills. Eventually, these chemicals destine to aquatic ecosystems, such as rivers, ponds, lakes, seas and oceans. Humans further get exposed to EDCs by eating marine products. The bio-accumulative and bio-magnification nature of EDCs result in their very high levels in large predatory fish and marine mammals. Studies show the people who regularly eat marine products contaminated with EDCs encounter various forms of adverse health outcomes such as thyroid hormone disruptions, infertility, and other endocrine diseases. Despite extensive literature available in industrialized countries, studies conducted in resource constraint countries are very few. Therefore, more research needed to generate further evidence.